Delusional infestation in the treatment of ADHD with atomoxetine - Howes, Catriona F (BMJ Case Rep, 2018)
The case describes an adult diagnosed with attention deficit hyperactivity disorder and treated with atomoxetine who quickly developed a florid case of delusional infestation. The patient described very distressing experiences that were significantly impacting her daily life. The symptoms improved with the withdrawal of atomoxetine and resolved completely with antipsychotic medications. Atomoxetine is proposed as the putative causative agent in this case.